THE ROLE OF SUPPLY CHAIN MANAGEMENT IN IMPROVING THE COMPANY'S OPERATIONAL EFFICIENCY - Wibowo, Edi; Nuswandari, Inti; Maidarti, Titin (JURNAL EKBIS, 2024)
The purpose of this article is to understand: 1) The importance of supply chain management for companies; 2) What is the role of supply chain management in improving the operational efficiency of companies? This article uses qualitative research that uses literature review as its data collection method. Research has shown that the importance of supply chain management for companies is to ensure that products and services are optimally distributed to customers and to ensure that products are delivered when customers want them, reducing costs and increasing the company's profits in the supply chain. Optimizing time, space, and the amount of resources. All this so that companies can compete in an increasingly global business. The role of supply chain management in improving the company's operational performance is as follows: 1) Helping to identify potential problems that may arise. 2) Optimizing costs; 3) Efficiency and reduction of operational costs; 4) Improving the supply chain process through spatial awareness.